Consumer Responses to Scarcity Appeals in Online Ordering - Hariyana, Nanik; Izaak, Wilma Cordelia; Sholihah, Dienni Ruhjatini (Nusantara Science and Technology Proceedings, 2023)
Scarcity appeals, which highlight how a commodity or service is scarce due to "high demand" or "limited supply," are frequently used in the tourism industry. However, not all scarcity appeals have the same ability to persuade consumers. The current study investigates the combined effects of consumers' power perceptions and the supply- or demand-framed nature of scarcity appeal in the context of online booking. The results show that when presented with a demand-framed scarcity appeal vs a supply-framed one, customers with a strong sense of power are more likely to make a purchase; however, this difference is less noticeable for customers with a low sense of power. Furthermore, mediation analysis reveals perceived risk as the psychological mechanism behind these effects. The managerial ramifications of online booking systems are discussed.